Green Synthesis and Applications of Silver Nanoparticles Using Plant Extracts: A Review Article: Pharmaceutical Science-Pharmaceutics - Akshay; Verma, Anchal; Saroha, Akshay; Garg, Rajeev (International Journal of Life Science and Pharma Research, 2022)
The nanoparticle (NP) biosynthesis field is still underdeveloped and has long been known to impact many industries significantly. Recently, the synthesis of silver NPs has been given excessive attention in developed countries because of the requirement to develop environmental supporter technologies to synthesize materials. The uses of green chemicals are environmentally friendly, non-poisonous, and inexpensive. It has been shown that various microbes, including yeast, fungi, bacteria, and plants, can synthesize intracellular and extracellular AgNPs. All systematic information reflects the unique possessions of AgNPs, which have many uses such as antifungal, antibacterial, anticancer, and antiviral agents, brilliant natural catalytic larvae, dyedegrading, excellent antioxidants, treatment of complications associated with diabetes, and wound curative. Physical and chemical methods use high radiation levels and high concentrations of reducing agents and stabilizers that are dangerous to the environment and human health. Therefore, the synthesis of NPs is a one-step bioremediation approach and consumes low energy for an environmentally friendly synthesis of NPs. Recently, the development of effective green chemistry methods using reducing agents, limiters, and natural stabilizers to obtain AgNPs of good shape and sizes has become an area of research. This review aims to explore the green synthesis of silver nanoparticles using plant extract, and the characterization of synthesized silver nanoparticles with their different applications. Also, this review is meant to tell about the plants and their various parts that can be used for the green chemistry of silver nanoparticles in an environmentally friendly basis with their many therapeutic applications. Finally, this review summarizes the latest published data that can be used for research.